2008
DOI: 10.1017/s0022112008001900
|View full text |Cite
|
Sign up to set email alerts
|

Liquid interfaces in viscous straining flows: numerical studies of the selective withdrawal transition

Abstract: This paper presents a numerical analysis of the transition from selective withdrawal to viscous entrainment. In our model problem, an interface between two immiscible layers of equal viscosity is deformed by an axisymmetric withdrawal flow, which is driven by a point sink located some distance above the interface in the upper layer. We find that steady-state hump solutions, corresponding to selective withdrawal of liquid from the upper layer, cease to exist above a threshold withdrawal flux, and that this tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…In his work, the suction is represented by a point sink. More recently, several experimental and numerical studies have dealt with well-controlled Newtonian liquid-liquid systems [1,[5][6][7] and gas-liquid systems [8][9][10]. For liquid-liquid systems, the flow behavior may be classified into three regimes: subcritical, critical and supercritical (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his work, the suction is represented by a point sink. More recently, several experimental and numerical studies have dealt with well-controlled Newtonian liquid-liquid systems [1,[5][6][7] and gas-liquid systems [8][9][10]. For liquid-liquid systems, the flow behavior may be classified into three regimes: subcritical, critical and supercritical (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The critical state is the threshold for the uptake of the interface. The hump height in the subcritical regime and the critical flow rate have been measured and computed [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…We mimic the effect of a deep lower layer by requiring that a constant pressure jump, of size p 0 , be maintained across the internal fluid surface I b . A previous study [11] has tested this model extensively against the experimental situation and found that it reproduces the measured dynamics, with the model parameter p 0 and the pinning condition, having little effect on the outcome. Here, we focus on the results for Q c .…”
mentioning
confidence: 95%
“…The bulk flow in both layers then satisfies the linear Stokes flow equations, which we solve using a Green's function formulation [18]. The numerical formulation follows that devised by Kleine Berkenbusch, Cohen, & Zhang, and the full description can be found in the earlier study [11]. The key steps are that we first obtain an expression for the velocity on the fluid interface as an integral over a closed surface formed by the fluid interface, I f and the back surface I b .…”
mentioning
confidence: 99%
“…While many studies focused on Newtonian fluids (Xue and Yue 1998;Zhou and Graebel 1990;Robinson et al 2010), only a few papers studied non-Newtonian fluids withdrawal. However, they were restricted in the investigation of surface/interface deformation and force balance (Zhou and Feng 2010;Blanchette and Zhang 2009;Berkenbusch et al 2008;Jeong 2007). There have been no experimental studies to examine the flow field of a non-Newtonian flow withdrawing near an intake.…”
Section: Introductionmentioning
confidence: 99%